The Extent of Compliance of the Public Procurement Act, Act 663 of 2003: A Case of Tamale Central Hospital - Seidu, Princess Barikisu (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters in Public Administration,